2012
DOI: 10.1200/jco.2012.30.15_suppl.5064
|View full text |Cite
|
Sign up to set email alerts
|

Application of an ointment with high radical protection factor as a prevention strategy against PPE.

Abstract: 5064 Background: Pegylated liposomal doxorubicin has proved to be highly efficient in the treatment of various tumors. Depending on the application protocol, up to 80% of patients develop palmar-plantar erythrodysesthesia (PPE). So far, a prevention strategy is still unknown. Recently, it was shown that parts of the chemotherapeutics were excreted with the sweat onto the skin surface, spreading there homogeneously and penetrating into the stratum corneum. The formation of free radicals in the tissue results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The measurement system could be used for the indication to initiate a prevention strategy of cutaneous toxicities in the form of topical application of antioxidants. 29,30 The results obtained show that some of the fluorescence-active chemotherapeutic agents, for example, doxorubicin or epirubicin can be detected due to enhanced skin fluorescence as expected. 31 The direct detection and identification of all fluorescence-free chemotherapeutic agents in the skin using SERRDS was not observed within this study and can be subjected to further investigations.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The measurement system could be used for the indication to initiate a prevention strategy of cutaneous toxicities in the form of topical application of antioxidants. 29,30 The results obtained show that some of the fluorescence-active chemotherapeutic agents, for example, doxorubicin or epirubicin can be detected due to enhanced skin fluorescence as expected. 31 The direct detection and identification of all fluorescence-free chemotherapeutic agents in the skin using SERRDS was not observed within this study and can be subjected to further investigations.…”
Section: Discussionsupporting
confidence: 61%
“…In summary, the applied SERRDS measurements showed excretion of intravenous chemotherapeutic agents on the skin surface by simultaneously analyzing the carotenoid antioxidants and the fluorescence in the skin. The measurement system could be used for the indication to initiate a prevention strategy of cutaneous toxicities in the form of topical application of antioxidants …”
Section: Discussionmentioning
confidence: 99%
“…The latter was demonstrated to be caused by the excretion of parts of cytotoxic agents with the sweat onto the skin surface spreading there homogeneously and penetrating into the stratum corneum. This led to disturbance preferably in ‘vulnerable' body areas with thick stratum corneum such as the palm and the planta ( Kluschke et al , 2012 ; Lademann et al , 2012 ). Having said, this may point towards new prophylactic measures for the prevention of HFSR using antioxidant containing ointments with high radical protection factor.…”
Section: Discussionmentioning
confidence: 99%
“…It was assumed that the preventive topical application of antioxidants can neutralize the formed ROS within the SC before they can destroy cells or cell compartments. In a pilot study on 20 patients that were diagnosed with ovarian cancer that were treated with pegylated liposomal doxorubicine (40 mg/m 2 , 4 cycles) [ 229 ], it was shown that the topical application of a cream containing a balanced antioxidant mixture (Mapisal, Medac GmbH, Wedel, Germany) twice daily can significantly reduce the occurrence and severity of PPE [ 230 ]. The antioxidant mixture that was used in the cream was characterized by a very high free radical protection factor of 4500 × 10 14 radicals/mg.…”
Section: Factors Resulting In the Reduction Of Carotenoids In The Scmentioning
confidence: 99%